Fernán Caballero y la defensa de la causa animal como proyecto nacional en «Los pobres perros abandonados» (1865) - Julie Botteron (Cuadernos de Ilustración y Romanticismo)
In her article «Los pobres perros abandonados» (1865), Fernán Caballero develops a critique of the cruelty towards dogs in Spain. The author plays with the feminine and maternal perspective offered by a magazine such as El Ángel del Hogar to talk about the identity construction of Spain as a civilized nation through the case of animal abuse. By means of a literary game which includes Antoine de Latour, Miguel de Cervantes and Dulcinea, a descendant of the dogs of El coloquio, she aims to display various educative purposes, and in particular the moral problem and consequent danger constituted by modern novels.